Grid Connection of Wave Power Farm Using an N-Level Cascaded H-Bridge Multilevel Inverter - Rickard Ekström; Mats Leijon (Journal of Electrical and Computer Engineering)
An N-level cascaded H-bridge multilevel inverter is proposed for grid connection of large wave power farms. The point-absorber wave energy converters are individually rectified and used as isolated DC-sources. The variable power characteristics of the wave energy converters are discussed, and a method of mitigating this issue is demonstrated. The complete power control system is given in detail and has been experimentally verified for a single-phase setup of the 9-level inverter. Theoretical expressions of the power sharing between multilevel cells are derived and show good correspondence with the experimental results.